The dynamic effect of information and communication technology and renewable energy on CO2 emission: Fresh evidence from panel quantile regression - Wen, Yuzhao; Shabbir, Malik Shahzad; Haseeb, Mohammad; Kamal, Mustafa; Anwar, Ahsan; Khan, Mohammad Faisal; Malik, Summaira (Frontiers in Environmental Science, 2022)
Since last few years, the rapid growth of information and communication technologies (ICT) contributes in every sector of the economy; though, the environmental consequences ICT may not be overlooked. In doing so, this research investigates the asymmetric impact of ICT, renewable energy consumption (RENE), economic growth (GDP), financial development (FD), and population (POP) on CO2 emissions (CE) in the MINT countries over the period from 1990 to 2018. For this purpose, this study uses STIRPAT and Quantile Regression. The preliminary outcomes reject the assumption of data normality; therefore, it is very necessary to use the Quantile regression (QR), as the QR technique can deal with structural changes, outliers, and data non-normality. The results of QR indicate that ICT reduce carbon emissions across all the quantiles (1st quantile to 9th quantile). Similarly, RENE also impedes the carbon emissions across all (1st to 9th) quantiles. On the other hand, FD, GDP, and POP increases the carbon emissions across all the quantile (1st to 9th). These outcomes purposed appropriate policy implications for MINT countries.